Search for the neutral Higgs boson at LEP - Dova, María Teresa (1992)
A search for the standard model neutral Higgs boson is described. Data collected during 1990 and 1991, corresponding to 408 000 hadronic decays of the Z°, were used. At the 95% confidence level we exclude the existence of the minimal standard model Higgs boson in the mass range 0⩽MH0<52 GeV.